The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3329/bsmmuj.v9i4.30060
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation, linguistic and clinimetric validation of the Bangla version of Zarit Burden Interview

Abstract: The aim of this study was to develop a culturally adapted and validated Bangla version of Zarit Burden Interview (ZBI-B) questionnaire for use in Bangla speaking caregiver of patient with dementia. This study was conducted on 100 caregivers related to consecutively attending outpatients with a previously established primary diagnosis of dementia, according to DSM-IV criteria. Validity and reliability were evaluated by comparing with the caregiver burden inventory (CBI). An exploratory factor analysis with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The Zarit-MOR factor analysis extracted seven principal components with an eigenvalue ≥1, which explain 77.838% of the total variance. These results are close to the Bengali version of Zarit scale indicating that six components with an eigenvalue ≥1 represent 69% of the total variance [11].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The Zarit-MOR factor analysis extracted seven principal components with an eigenvalue ≥1, which explain 77.838% of the total variance. These results are close to the Bengali version of Zarit scale indicating that six components with an eigenvalue ≥1 represent 69% of the total variance [11].…”
Section: Discussionsupporting
confidence: 78%
“…The alpha coefficient of this study was low because the investigation was conducted in a single medical center in a single geographical area and with caregivers of patients with a different disease. Similarly, in [11], a Bengali version realized with 100 caregivers of patients with dementia. This study found an alpha and ICC coefficient of 0.8 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other named factors include: 'embarrassment/anger', 'patient's dependency', 'captivity', 'loss of control' and 'guilt'/'self-criticism'/'inadequacy' (Cheng et al, 2014;Flynn Longmire & Knight, 2011;Rabin et al, 2016;Torres et al, 2012). Comparatively, in the aforementioned studies, the numbers of factors reported in studies from developing country settings appear to be greater than those from developed countries.…”
Section: What This Paper Addsmentioning
confidence: 94%
“…Initially, a baseline study was conducted to assess the caregiving burden among female informal caregivers of cancer patients. Subsequently, in this study, individual caregivers are enrolled based on their experiences with mild-to-moderate, moderate-to-severe, and severe burdens, as determined using the Bangla version of the Zarit Burden Interview (ZBI)-22 [ 22 ]. The inclusion criteria were as follows: females aged 18 years or older and those who have been providing care to a cancer-diagnosed patient for at least six months.…”
Section: Methodsmentioning
confidence: 99%
“…Data on caregivers' sociodemographic characteristics includes age, marital status, education level, employment status, monthly family income, presence of chronic diseases, relationship with the patient, duration of caregiving (months), and daily caregiving time (hours). Moreover, the ZBI-22 [ 22 ], Hospital Anxiety Depression Scale (HADS) [ 24 ], and World Health Organization Quality of Life Instrument (WHOQOL-BREF) [ 25 ] will be used to assess the level of burden, anxiety, depression, and QOL, respectively, all of which were validated and adopted in the local language, Bengali.…”
Section: Methodsmentioning
confidence: 99%